Mapping Strategic Development Of Sustainable Rural Tourism In Indonesia: A Swot Analysis - Andy Mulyana; Ahmad Soleh; Ida Ayu Made Er Meytha Gayatri; Yulita Suryantari; Fondina Gusriza (Journal of Business on Hospitality and Tourism, 2026)
Sustainable rural tourism has become an important strategy for promoting local economic development while preserving environmental and socio-cultural resources. This study aims to identify strategic sustainable tourism development in Indonesia through a case analysis of four tourist villages: Penglipuran (Bali), Nglanggeran (Yogyakarta), Setanggor (West Nusa Tenggara), and Belitar Seberang (Bengkulu), which represent diverse rural tourism contexts. Using a SWOT (Strengths, Weaknesses, Opportunities, Threats) framework, the study analyzes internal and external factors influencing tourism development. Primary data were obtained through in-depth interviews with key stakeholders, including village tourism managers, local government authorities, and local community members. The results indicate that the villages are positioned in the First Quadrant, reflecting strong internal resources and favorable external opportunities for sustainable growth. Nevertheless, several internal limitations and external risks persist, particularly in institutional capacity and long-term management. This study contributes empirically by integrating sustainability dimensions into SWOT-based strategic planning across diverse tourism village contexts and provides practical guidance for policymakers and local stakeholders in developing collaborative and resilient rural tourism strategies in Indonesia.